Phenotypic plasticity of the coral Porites rus: Acclimatization responses to a turbid environment - Padilla-Gamiño, J.; Hanson, K.; Stat, Michael; Gates, R. (2012)
Increasing terrestrial runoff due to anthropogenic activities has become a major problem for coral reef ecosystems around the world. Turbidity due to runoff can reduce light availability (via nutrient enrichment and sedimentation) and influence the biology and ecology of coral reefs. In this study, we explored the physiology and acclimatization potential of Porites rus, a morphologically variable reef-building coral that is common in Moorea, French Polynesia, and a species that thrives across turbidity gradients driven by proximity to terrestrial runoff. We compared tissue biomass, Symbiodinium identity, Symbiodinium density, chlorophyll concentrations, and stable isotope ratios in plating and branching areas of colonies sampled in turbid and non-turbid environments. A reciprocal transplant experiment (RTE) was also employed to compare the acclimatization capacity of P.rus from turbid and non-turbid environments. Our results indicate that the physiological differences between plating and branching regions within individual colonies of P. rus are greater than those of colonies from turbid and non-turbid environments. Plating regions of colonies had larger tissue biomasses than branching areas, regardless of environment. Plating regions also had higher chlorophyll concentrations than branching regions at the non-turbid site. The densities and genetic identity of Symbiodinium were the same at both sites. At the turbid site, d 13C signatures were lower in plating than branching regions of the colony, suggesting they exhibit different rates of photosynthesis and/or capacity for heterotrophy. d 15N were similar across sites and between morphologies, indicating that colonies from both sites were feeding at similar trophic levels and utilizing similar nitrogen sources. The RTE showed that P. rus acclimatizes differently when transplanted to the turbid and non-turbid environments. Corals from the non-turbid site grew less when transplanted to the turbid site, whereas corals from the turbid site showed no change in growth regardless of transplant location. Coral fragments transplanted to the non-turbid site, had lower levels of chlorophyll per tissue area than fragments transplanted to the turbid site, most likely reflecting the higher light levels at this site. Thus, our results demonstrate that there is significant variation in the physiology of P.rus at the colony level (branching vs. plate regions) and at the site level (turbid vs. non-turbid) and that this species can acclimatize to changes in environmental conditions on short time scales (weeks). This acclimatization potential may play an important role in enabling this coral species to diversify strategies for energy acquisition within the colony and facilitate persistence in turbid environments. © 2012 Elsevier B.V.